2005
DOI: 10.4067/s0716-97602005000200019
|View full text |Cite
|
Sign up to set email alerts
|

Wheel-running and rest activity pattern interaction in two octodontids (Octodon degus, Octodon bridgesi)

Abstract: Wheel-running and other non-photic stimuli influence the rest-activity pattern of diurnal and nocturnal mammals. A day to night inversion of phase preference of activity was described among Octodon degus, when exposed to ad-libitum wheel running. We have studied the rest-activity pattern response in presence of ad libitum wheel-running in wild-captured male individuals from two species of genus Octodon: O. degus (n=9, crepuscular-diurnal) and O. bridgesi (n=3, nocturnal). After two months of habituation to lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
(15 reference statements)
1
11
0
Order By: Relevance
“…This wheelinduced phase-switch was replicated in two other experiments with laboratory-born animals (Kas & Edgar 1998, as well as in one experiment examining wild-caught degus (Ocampo-Garces et al 2005), suggesting that it is not an isolated phenomenon caused by inbreeding. However, it is certainly caused by laboratory conditions.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…This wheelinduced phase-switch was replicated in two other experiments with laboratory-born animals (Kas & Edgar 1998, as well as in one experiment examining wild-caught degus (Ocampo-Garces et al 2005), suggesting that it is not an isolated phenomenon caused by inbreeding. However, it is certainly caused by laboratory conditions.…”
mentioning
confidence: 64%
“…Other investigators have found that the degu shows diurnal rhythms in temperature and locomotor activity in the laboratory using methods of biotelemetry (Refinetti 1996;Kas & Edgar 1998;Kas & Edgar 1999). However, when the degus were given access to a running wheel, the observed rhythms frequently became crepuscular or nocturnal (Kas & Edgar 1998, 1999Garcia-Allegue et al 1999;Ocampo-Garces et al 2005; Figure 1). Kas and Edgar (1999) closely observed this phase-switching phenomenon in response to ad libitum wheel access.…”
Section: Biological Rhythm Research 273mentioning
confidence: 90%
See 1 more Smart Citation
“…40 Similar to observations on Mongolian gerbils, at least two investigations have reported degus to become nocturnal in the laboratory simply upon gaining access to a running wheel. 41,42 However, approximately half of the degus in two other studies were diurnal and half were nocturnal regardless of the presence or absence of running wheels, apparently as a matter of individual peculiarity. 30,41 Thus, although degus appear to be more diurnal than Mongolian gerbils, they do not seem to be reliably and consistently diurnal under laboratory conditions.…”
Section: Resultsmentioning
confidence: 89%
“…More exaggerated chronotype flexibility is reported in the laboratory due to housing and lighting variables ( e.g ,. Kas and Edgar, 1999; Ocampo-Garces, 2005; Hagenauer and Lee, 2008). …”
Section: Discussionmentioning
confidence: 99%